Field reports, Spring 1993, Dennis Carter - Carter, Dennis L.et al (1993)
An annotated list of birds sighted by Dennis Carter dated June 1, 1993. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1993. Plustek - flatbed